Do different flap designs have negligible impacts on the removal of mandibular third molars? - Seta, Astrodita Adya; Arindra, Pingky Krisna; Haryosuwandito, Erdananda (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
This study aims to evaluate various flap incision techniques utilized in the mandibular third molar removal surgery. A systematic review with a qualitative approach was conducted. Data were obtained from published journals through manual database searches via Scopus, ScienceDirect, and PubMed covering the period from 2000 to 2024, using predetermined keywords related to the topic. The PRISMA statement guidelines were followed, including the use of the official flow chart. Twenty-one journals were identified and analyzed to compare different flap designs in mandibular third molar extraction procedures, focusing on their relationship with wound healing processes and complication rates. Comparative analysis of flap incision techniques was performed through systematic evaluation of multiple journal data. Both envelope and triangular flaps demonstrated comparable healing times in third molar extraction procedures. The envelope flap, while minimally invasive, showed association with dry socket occurrence. The triangular flap provided superior surgical access and demonstrated pain reduction following mandibular third molar surgery. The pedicle flap showed effectiveness in preventing dry socket and alveolar osteitis. In addition, the Lingual-based triangular flap proved superior to buccal-based triangular flap in controlling postoperative pain, swelling, and trismus while reducing overall complications. This analysis demonstrates that flap design selection significantly influences postoperative outcomes in mandibular third molar surgical procedures. Both triangular and envelope flap can be considered for the procedure of mandibular wisdom teeth removal.